Enhancing the socio-economic wellbeing of Malaysian local women through social capital and microEnterprise performance - Isidore Ekpe; Norsiah Mat; Abdullah Al- Mamun; Nik Malini Nik Mahdi (http://fkp.umk.edu.my/journal/download/2-v3i2.pdf, 2015)
This study aims to determine the influence of social capital on women’s micro-enterprise performance in the state of Kelantan, Malaysia. The moderating effect of attitude on the relationship between social capital and women’s micro-enterprise performance is also assessed. The study employed a cross-sectional survey design, with simple random sampling, to collect data from 385 women entrepreneurs in Kelantan. The study spanned from 2014 to 2015 and data were collected between February and May, 2015. Descriptive statistics, t-test, and Smart PLS were used to analyze the data. The result of the study, among others, indicates that social capital has a significant positive effect on micro-enterprise performance. The study recommends, among others, that the Malaysian government should create awareness among women about the existence and benefits of women’s associations regarding business activities, especially in the local areas.